Effect of Temperature and Humidity on Rigor Mortis: A Retrospective Medicolegal Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Rigor mortis is considered to be one of the early signs of death. Rigor mortis or post-mortem stiffening is a physico-chemical process involving both voluntary and involuntary muscles of the body. Though it is a reliable tool of estimating post-mortem interval, its onset, development and disappearance is affected by many external and internal factors. Temperature and humidity of the place from where body is recovered or where it remains after death plays an important role in the development of rigor mortis, which further affects the estimation of post-mortem interval.
Keywords: Rigor mortis; Stiffening; Temperature; Post-mortem Interval; Estimation; Amritar